Gender differences in the association between dietary protein intake and constipation: findings from NHANES - Hong, Yongping; Shen, Hongchen; Chen, Xingxing; Li, Guofeng (Frontiers in Nutrition, 2024)
Purpose: Dietary factors play a crucial role in the development and management of chronic constipation, yet the relationship between dietary protein intake and constipation remains underexplored. This study aims to investigate the association between dietary protein intake and the prevalence of constipation among American adults, with a focus on potential gender differences, using large-scale national data.Data from 14,048 participants aged 20 and above (7,072 men and 6,976 women) from the National Health and Nutrition Examination Survey (NHANES) 2005-2010 were analyzed. The Bristol Stool Form Scale's types 1 (separate hard lumps, resembling nuts) and 2 (sausage-shaped, but lumpy) were used to define constipation. A 24-hour dietary recall technique was used to measure dietary protein intake. After controlling for covariates, the association between protein consumption and constipation risk was examined using multivariable logistic regression, smooth curve fitting, and testing for gender interaction effects. We then further determined the threshold effect between dietary protein intake and constipation risk.Results: Constipation was present in 7.49% of people overall, with a higher proportion among women (10.19%) than among males (4.82%). In men, higher protein intake was significantly associated with a lower rate of constipation. However, in women, higher protein intake correlated with an increased risk of constipation, and the interaction between gender was significant (P for interaction = 0.0298). These results were corroborated by smooth curve fits, which also demonstrated a dose-response effect. Further threshold effect analysis showed that the turning points of dietary protein intake differed between male and female participants (119.42 gm/day for men; 40.79 gm/day for women).The association between dietary protein intake and constipation was different in different genders with threshold effect. For men, moderately increasing protein intake could be beneficial, while for women, exceeding a certain level may increase the risk of constipation. These insights are crucial for guiding dietary protein recommendations for different genders and have significant clinical implications.